Roadmaps and Detours: Active Chlorophyll- a Assessments of Primary Productivity Across Marine and Freshwater Systems - Hughes, David J; Campbell, Douglas A; Doblin, Martina A; Kromkamp, Jacco C; Lawrenz, Evelyn; Moore, C Mark; Oxborough, Kevin; Prášil, Ondřej; Ralph, Peter J; Alvarez, Marco F; Suggett, David J (Environmental science & technology, 2018)
Assessing phytoplankton productivity over space and time remains a core goal for oceanographers and limnologists. Fast Repetition Rate fluorometry (FRRf) provides a potential means to realize this goal with unprecedented resolution and scale yet has not become the "go-to" method despite high expectations. A major obstacle is difficulty converting electron transfer rates to equivalent rates of C-fixation most relevant for studies of biogeochemical C-fluxes. Such difficulty stems from methodological inconsistencies and our limited understanding of how the electron requirement for C-fixation (Φe,C) is influenced by the environment and by differences in the composition and physiology of phytoplankton assemblages. We outline a "roadmap" for limiting methodological bias and to develop a more mechanistic understanding of the ecophysiology underlying Φe,C. We 1) re-evaluate core physiological processes governing how microalgae invest photosynthetic electron transport-derived energy and reductant into stored carbon versus alternative sinks. Then, we 2) outline steps to facilitate broader uptake and exploitation of FRRf, which could transform our knowledge of aquatic primary productivity. We argue it is time to 3) revise our historic methodological focus on carbon as the currency of choice, to 4) better appreciate that electron transport fundamentally drives ecosystem biogeochemistry, modulates cell-to-cell interactions, and ultimately modifies community biomass and structure.
Keywords: chlorofyl a; Phytoplankton; chlorofyl; ekosystém; Fresh Water; Ecosystem; Chlorophyll A; Photosynthesis; fytoplankton; Chlorophyll; sladká voda; fotosyntéza